- Download PDF
2 Answers | Add Yours
Solve the first equation for `x: x=4y+4`
Substitute this expression for `x` into the second equation:
`6(4y+4)-3y=-18` You now have one equation in one unknown. Solve for `y:`
So the solution is x=-4,y=-2
Check by plugging back into both equations:
So just pick a variable that is easy to isolate. Since X in the first equation is all by itself and all we have to do is add 4y to both sides to find its value I'll go with the first equation to solve for X this will then give you
You now have the value of X so you can plug it into the second equation giving you
6 (4y +4) -3y=-18
You then simplify and solve for y.
Y=-2 you then take this and plug it into the first equation x-4y=4
X-4 (-2)= 4
Then plug the x and y values into both equations to double check that the answers match.
We’ve answered 320,516 questions. We can answer yours, too.Ask a question